The Phonological of Patani Malay Dialect: An Analysis Of Autosegmental Theory - Dr. Suraiya Chapakiya (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2020)
This paper aims at identifying and determining Malay dialect phonemes and the syllable structure of Patani Malay Dialect (PMD). The study is also conducted to analyze the phonological processes of PMD. The researcher used The autosegmental theory based on distinctive feature geometry model by Halle (1995), Clément’s representation level of syllable structure (1985) and, Zaharani and Teoh Boon Seongs’ building of syllable structure (2006). A qualitative method was used in this study. The data were collected from the field work where observations and interviewing were carried out. The results show that the PMD can be divided into three vowel phoneme categories. The first vowel phoneme category consists of six vowel phonemes. They are /i/, /e/, /a/, /«/, /o/, /u/. The second vowel phoneme category has two derived vowel phonemes such as [E], [] and the last vowel phoneme category consists of four nasalization vowels such as [u)], [E)], [)] dan [a)]. The study also found that PMD has 28 consonants. They can be grouped into three consonant categories. The first consonant category consists of 20 original consonants such as /p/, /t/, /k/, /b/, /d/, /g/, /c&/, /j&/, /s/, /l/, /r/, /Ä/, /m/, /n/, /N/, /ø/, /w/, /j/, /h/, ///. The second consonant category has four aspiration consonants such as /ph/, /th/, /kh/, /ch/. The third consonant category has four loan consonants such as /f/, /z/, /x/, /S/. While the syllable structure of PMD is categorised as type III which is a pattern of CV(C) syllable. The study suggests that the  phonological processes of PMD identified and analysed based on the autosegmental theory have the characteristics of assimilation, vowels nasalizasion, deletion, glottalisation, monophthongisation and vowels changing.